2009
DOI: 10.1038/gt.2009.108
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid–spermine conjugates as DNA carriers for nonviral in vivo gene delivery

Abstract: The lack of efficient in vivo gene delivery is a well-known shortcoming of nonviral delivery vectors, in particular of chemical vectors. We developed a series of novel nonviral carriers for plasmid-based in vivo gene delivery. This new transport device is based on the assembly of DNA plasmids with synthetic derivatives of naturally occurring moleculesfatty acid-spermine conjugates (or lipospermines). We tested the ability of these fatty acid conjugates to interact with plasmid DNA (pDNA) and found that they fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…siRNA with a negative charge binds to the positively charged nitrogen of C12‐SPM to form self‐assembled nanoparticle complexes via electrostatic interactions. A previous study reported that conjugation of fatty acids to SPM improved binding and condensation of SPM to DNA, supporting the use of this fatty acid–spermine conjugate for DNA delivery . Gel retardation assays indicated that C12‐SPM could efficiently form siRNA complexes at different weight ratios of siRNA to lipidoids (1:2.5, 1:5, 1:7.5, and 1:10) (Figure b).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…siRNA with a negative charge binds to the positively charged nitrogen of C12‐SPM to form self‐assembled nanoparticle complexes via electrostatic interactions. A previous study reported that conjugation of fatty acids to SPM improved binding and condensation of SPM to DNA, supporting the use of this fatty acid–spermine conjugate for DNA delivery . Gel retardation assays indicated that C12‐SPM could efficiently form siRNA complexes at different weight ratios of siRNA to lipidoids (1:2.5, 1:5, 1:7.5, and 1:10) (Figure b).…”
Section: Resultssupporting
confidence: 55%
“…To prepare the lipidoids, alkyl epoxides were conjugated to polyamines. Because polyamines condense polynucleotides due to their cationic characteristics, they are expected to contribute to lipidoid complex formation with siRNA. In the epoxide ring‐opening reaction, oxide radicals of alkyl epoxides react with the amine groups of polyamines and, accordingly, alkyl epoxide tails chemically conjugate to primary and secondary amines of polyamines at 90 °C (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…We first verified possible interactions between DNA and Dapa 8 peptides by an electrophoresis shift-assay that showed that all Dapa 8 peptides interacted with plasmid DNA. Similar to fatty acid-spermine conjugates (Viola et al, 2009), this interaction was concentration dependent and was more evident with increasing length of the alkyl chains. The formation of DNA particles was confirmed by DLS studies.…”
Section: Manuscript IVmentioning
confidence: 80%
“…All DNA complexes were characterized by an average diameter between 75 and 170 nm and were stable over 24h. Surprisingly, even palmitoyl-conjugated Dapa 8 formed stable and well-defined particles (with an homogeneous distribution), whereas palmitoylconjugated spermines (Viola et al, 2009) resulted in a heterogeneous and largesized population.…”
Section: Manuscript IVmentioning
confidence: 95%
“…After rotaevaporation of the solvent the crude product is purified by flash chromatography (petroleum ether/diethyl ether ¼ 4:1) to yield colorless oils with an intense odor. 24.8 (t), 28.9 (t), 29.0 (t), 29.1 (t), 33.9 (t), 34.1 (t), 51.3 (q, OCH 3 , C-1), 54.4 (q, OCH 3 , Pd 2 (dba) 3 CHCl 3 (24 mg, 0.023 mmol) and triphenylphosphine (52 mg) are dissolved under argon in absolute (abs.) tetrahydrofuran (2 mL).…”
Section: General Proceduresmentioning
confidence: 99%